Use of Articaine in loco-regional anesthesia for day care surgical procedures - Sukhminder Jit Singh Bajwa; Ravi Jindal (Wolters Kluwer Medknow Publications, 2012)
The popularity of day case surgical procedures has increased immensely over the last few years. Though various techniques are available for carrying out day-case anesthesia, preference for a technique depends upon the type of procedure, patient profile, associated co-morbidities, available infrastructure and back-up facilities, monitoring devices and comfort of the attending anesthesiologist with the technique. Day-case spinal anesthesia for ambulatory surgery has gained a wider acceptance and numerous drugs are available for use in loco-regional anesthesia. Articaine is one such amide local anesthetic drug which is increasingly being used in day care surgeries. Properties of articaine such as faster onset, shorter elimination time and rapid recovery from sensory and motor blockade make it a very useful agent in local and regional anesthesia for day care surgical procedures. This article aims to review these properties of articaine so as to evaluate how useful articaine can be for ambulatory surgical procedures.